Is the time of calling helpful for differentiating transient ischaemic attack and stroke from mimics in primary care out-of-hours services? A cross-sectional study. Issue 12 (17th December 2020) - Erkelens, Daphne CA; Zwart, Dorien L; van der Meer, Gerben H; Wouters, Loes TCM; De Groot, Esther; Damoiseaux, Roger AMJ; Hoes, Arno W; Rutten, Frans H
Abstract : Objectives: Telephone triage of patients suspected of transient ischaemic attack (TIA) or stroke is challenging. Both TIA and stroke more likely occur during daytime, with a peak in the morning hours. Thus, the time of calling might be a helpful determinant during telephone triage. We assessed the time of calling in patients with stroke-like symptoms who called the out-of-hours services in primary care (OHS-PC), and evaluated whether the time of calling differed between patients with TIA or stroke compared with those with mimics. Design: Cross-sectional study. Setting: Six OHS-PC locations in the Netherlands. Participants: 1269 telephone triage recordings of patients calling the OHS-PC because of stroke-like symptoms. We collected information on patient characteristics, symptoms, time of calling and urgency allocation. The final diagnosis related to each triage call was based on letters from the neurologist (retrieved from the patient's general practitioner). Primary and secondary outcome measures: The primary outcome measures were the time of calling hourly and 4 hourly, and the risk of TIA or stroke/hour. The secondary outcome measure was the risk ratio of TIA or stroke in the morning (08:00—12:00h) versus other hours. Results: Mean age was 68.6 (SD±18.5) years, 56.9% were women and 50.0% had a TIA or stroke. The risk ratio of TIA or stroke among people calling with stroke-like symptoms between 08:00—12:00h versus other hours was 1.13 (95% CI 1.00 to 1.28, p=0.070). After correction for age and sex, the adjusted risk ratio was 0.94 (95% CI 0.80 to 1.10, p=0.434). Conclusion: In patients who called the OHS-PC because of stroke-like symptoms, the time of calling did not differ between patients with TIA or stroke and patients with mimics. Trial registration number: The Netherlands National Trial Registry (NTR7331).